BEBERAPA FAKTOR INTERNAL YANG MEMPENGARUHI UNMET NEED DI PROVINSI BALI - Manuati Dewi, Gst. Ayu (PIRAMIDA; Vol. 1, No. 2 Desember 2005)
The shifting of paradigm of Familiy Planning Program from quantity oriented toward quality oriented, makes family palnning service issue become more crucial. Family planning service obtained by community member affect unmet need proportion . Especially in Bali Province, unmet need proportion getting bigger, i.e from 5,8 percent in 1997 become 6,9 percent in 2002. This condition must be overcome soon because it tends to decrease family planning prevalence rate. Factors related to family planning service which affect unmet need is called internal factor. These factor consist of (1) availability of contraceptive devices, (2) technical skill rate of provider, (3) availability of information about possible side effect , (4) availability of information about service sources, (5) availability of information about the strength and weakness of each contarceptive devices, (6) availability of information about safety of method, (7) satisfaction rate of client, and (8) motivation given by provider. The amount of respondent in this study is 500 person, 100 person taken from each regencies i.e Karangasem, Jembrana, Buleleng, Gianyar, dan Badung. Sapling method applied in this study is non probability sampling through accidental sampling. Technique of analysis used is both quantitative and qualitative analysis. The finding shows that five out of eight factors analized affect unmet need prevalence. Those factors are (1) availability of information about possible side effect, (2) availability of information about service sources, (3) availability of information about the strength and weakness of each contarceptive devices, (4) availability of information about safety of method, and (5) motivation given by provider. Additionally, recommendation is given related to five target groups which are need to be intervent and also technique of intervention to be done for each of teh target group.
Keywords: unmet need, internal factor, family planning